Gotti's boys : the mafia crew that killed for John Gotti - DeStefano, Anthony M (Citadel Press, 2019)
They called him the “Teflon Don.” But in his short reign as the head of the Gambino crime family, John Gotti wracked up a lifetime of charges from gambling, extortion, and tax evasion to racketeering, conspiracy, and five convictions of murder. He didn<U+2019>t do it alone. Surrounding himself with a rogues gallery of contract killers, fixers, and enforcers, he built one of the richest, most powerful crime empires in modern history. Who were these men? Pulitzer Prize-winning journalist Anthony M. DeStefano takes you inside Gotti<U+2019>s inner circle to reveal the dark hearts and violent deeds of the most remorseless and cold-blooded characters in organized crime. Men so vicious even the other Mafia families were terrified of them. Meet Gotti<U+2019>s Boys . . . * Charles Carneglia: the ruthless junkyard dog who allegedly disposed of bodies for the mob<U+2014>by dissolving them in acid then displaying their jewels. * Gene Gotti: the younger Gotti brother who ran a multimillion-dollar drug smuggling ring<U+2014>enraging his bosses in the Gambino family. * Angelo “Quack-Quack” Ruggiero: the loose-lipped contract killer who was wire-tapped by the FBI<U+2014>and dared to insult Gotti behind his back. * Tony “Roach” Rampino: the hardcore stoner who looked like a cockroach<U+2014>and used his gangly arms and horror-mask face to frighten his enemies. * “Sammy the Bull” Gravano: the Gambino underboss who helped John Gotti execute Gambino mob boss Paul Castellano<U+2014>then sang like a canary to take Gotti down.